BEL452: Executive Summary Writing / Academy of Language Studies - UiTM, Academy of Language Studies (2012)
The course focuses on developing students’ ability to write executive summaries. Students are taught to summarize key information using a variety of texts such as articles from the Internet or discipline-based reports.